"Biting the Bullet" and Banning Guns: The Brazilian National Referendum of 2005 and Its Defeat at the Polls1. Issue 1 (20th April 2018) - Soltis, Katherine
Abstract: After the United Nations named Brazil the country with the highest number of gun deaths in the world in 1996, the Brazilian government set the date for the world's first and only national referendum to vote on gun prohibition in 2005. Although public opinion polls showed popular support levels over 80% just three months before the vote, the ban was surprisingly defeated with 64% of those who voted, or 59 million people, voting against it. To date, the existing studies on the disarmament issue have argued that the outcome reflected the success of the "No" Front's advertising messages that played off of widespread insecurity and violence, yet literature on other aspects of the disarmament movement remains limited. This study examines regional and state variation in voting results, showing the importance of overlooked cultural factors and finding that higher homicide rates and lower public security provision were associated with support for the ban. These results show that disarmament was not out of touch with civilian preferences as previous studies have concluded but was in fact an appealing public security response for Brazilians faced with crime and insecurity.